2015
DOI: 10.1002/cjce.22152
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of azeotropic behaviour by the inversion of functions from the plane to the plane

Abstract: Azeotropy is a thermodynamic phenomenon where liquid and vapour coexisting phases have the same composition. In binary mixtures, the azeotropy calculation is represented by a 2 Â 2 nonlinear system of algebraic equations with temperature (or pressure) and one molar fraction as unknowns. On rare occasions, this nonlinear system exhibits two solutions, characterizing a double azeotrope. In this work, we calculate double azeotropes with a geometry-based methodology: the numerical inversion of functions from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The azeotropic coordinates for the system HFC4130mee (1) + THF (2) at 35 kPa are ( 1 , ) = (0, 0924, 309, 45) (Azeotrope 1) and ( 2 , ) = (0, 255, 309, 57) (with T in Kelvin), as reported by Guedes, Moura Neto, and Platt (2015). As previously described as detailed by several authors (Segura et al, 2005;Guedes et al, 2015), two azeotropes appear at this pressure. We observed that the values for the azeotropic temperatures are extremely close, which can be a challenge for the algorithm.…”
Section: Azeotrope Calculationsupporting
confidence: 73%
“…The azeotropic coordinates for the system HFC4130mee (1) + THF (2) at 35 kPa are ( 1 , ) = (0, 0924, 309, 45) (Azeotrope 1) and ( 2 , ) = (0, 255, 309, 57) (with T in Kelvin), as reported by Guedes, Moura Neto, and Platt (2015). As previously described as detailed by several authors (Segura et al, 2005;Guedes et al, 2015), two azeotropes appear at this pressure. We observed that the values for the azeotropic temperatures are extremely close, which can be a challenge for the algorithm.…”
Section: Azeotrope Calculationsupporting
confidence: 73%
“…Factors that influence Guedes et al [3] Pure Temperature 315.71827 K 315.7 K Lu et al [4] Pure Pressure 101 325 Pa 101 kPa Kianinejad et al [5] Pure Porosity 52.47 % 52 % Abdelaziz et al [6] Pure Length 2.655 m 2.65 m Jeon et al [7] Analytical Surface area 163.9 m 2 · g −1 160 m 2 · g −1 Lin et al [8] Analytical EDS analysis 40.09 wt% 0.40 g · g −1 Jia et al [9] Analytical Viscosity 5.875 cP 5.9 cP Ma et al [10] Derived Selectivity 63.3 63 Vedoy and Soares [11] Derived Solids recovered 25.97 % 26 % Esmailpour et al [12] Derived Air density 0.921 02 kg · m −3 0.92 kg · m −3 Verma et al [13] Derived COD 1000.00 mg · L 1 .00 g · L Moradi et al [14] Derived Activation energy 36.314 kJ · mol…”
Section: Analytical Datamentioning
confidence: 98%
“…Missen [8] described an algebraic method devoted to the calculation of azeotropic coordinates for some common excess Gibbs free energy models. Guedes et al [9] analyzed-with a geometric approach, using the concept of functions from the plane to the plane-the existence of double azeotropy in two binary systems. Libotte et al [10] used geometrical concepts to explain the double retrograde vaporization phenomenon (another author rare and nonlinear thermodynamic phenomenon, which can occur in mixtures close to the critical point).…”
Section: Introductionmentioning
confidence: 99%
“…The focus of this work is essentially different from that employed by Guedes et al [9], which used some complex mathematical tools (such as homotopy-continuation methods) and highly nonlinear thermodynamic models, making it technically more difficult to demonstrate in elementary terms the basic geometric ideas involved in the azeotropy calculations. The azeotropy phenomenon in binary mixtures can be characterized by a nonlinear application of R 2 to R 2 , which motivates us to present some geometric notions on quadratic maps in the plane in Section 2.…”
Section: Introductionmentioning
confidence: 99%